The Effect of Adding Fly ash Waste And Additive Sikacim Concrete On The Compressive Strength Of CLC Type Lightweight Bricks - Lukma, Hazairin Nikmatul (Universitas Islam Balitar, 2024)
This study aims to determine the results of compressive strength testing between ordinary lightweight bricks compared to lightweight bricks with fly ash waste additives and sikacim concrete additives. The method used is the experimental method. In this study, test objects were made by adding fly ash waste and sikacim concrete additive as a mixture of lightweight brick material. Then the lightweight brick is tested for compressive strength at the age of 14 and 28 days, which is possible that the lightweight brick has reached the maximum compressive strength value. The data analysis used to determine whether or not the use of fly ash waste additives and sikacim concrete additives affects the compressive strength of lightweight bricks is regression analysis. In this study, 3 variations of test objects were made where each variation consisted of 5 test objects that had different mixture compositions, namely 0%, 25%, and 50%. The results of the comparison of the compressive strength of ordinary lightweight bricks with a mixture of fly ash waste and sikacim concrete additives for 14-day-old lightweight bricks, at 0% composition is 3.70 Mpa, and at the age of 28 days it increases to 4.43%. The compressive strength value at the age of 14 days for the 25% composition has increased to 4.38 Mpa and the 28-day old has increased compressive strength to 5.05 Mpa. While the 50% composition at the age of 14 days decreased by 16.15%, namely 3.09 Mpa, and those aged 28 days decreased by 17.60%, namely 3.65 Mpa.